SAT0268 CLINICAL FEATURES OF INTERSTITIAL LUNG DISEASE ASSOCIATED WITH KOREAN IDIOPATHIC INFLAMMATORY MYOPATHIES ACCORDING TO THE AUTOANTIBODY PROFILE. (June 2019) - Chung, Sang Wan; Kim, Jinhyun; Yoo, In Seol; Hong, Seung-Jae; Lee, Yeon-Ah; Kang, Seong Wook; Shim, Seungcheol; Choi, In Ah; Chang, Sung Hae
Abstract : Background: Myositis-specific and myositis-associated autoantibodies (MSA and MAA) have been used for more detailed classification and prediction of clinical course of idiopathic inflammatory myopathies (IIM). Interstitial lung disease (ILD) is known to be complicated with approximately 50% of IIM patients, having poor prognosis. Objectives: The aim of this study is to investigate clinical features of ILD in Korean adult patients with IIM according to the autoantibody profile including MSA and MAA. Methods: We conducted a multicenter cohort study including 108 adult patients (age≥18 years) who have been diagnosed as IIM by ENMC criteria MSA and MAA were screened with Immunoblot assay using Euroline strip (EUROIMMUN, Germany). Clinical information including the time of developing ILD and imaging findings of chest CT was reviewed using by medical record. Results: ILD was found in about half (52.8%, 57 of 108) of enrolled patients and closely associated with the presence of anti-ARS Abs, anti-MDA5 and anti-Ro52. Among 43 patients, Anti-ARS Abs were most common (46.5%) and included anti-Jo-1 (23.3%), -OJ (2.3%), -EJ (9.3%), -PL7 (14%), and -PL12 (7%) (Figure 1 ). To analyze the correlation of autoantibodies with pattern of ILD onset, we stratified the 43 patients into three groups: into ILD-preceding (7/43, 16.3%), simultaneous (31/43, 72.1%) and myopathy-preceding (6/43, 14%). In the ILD-preceding group, anti-ARS antibodies were frequent. ILD preceded myopathy by 19.5 months on average. The imaging pattern of ILD in the ILD-preceding group were Cryptogenic Organizing Pneumonia (COP) 6, Nonspecific Interstitial Pneumonia (NSIP) 1 and no Usual interstitial pneumonia ( UIP ). A half of patient in ILD-preceding group had Raynaud`s phenomenon, and one patient had mechanic hand. On the other hand, in myopathy-preceding group, 30% of patients (2/6) were UIP and a half of patients had pulmonary function which required treatment (DLCO <65%). Conclusion: In our study, ILDs were accompanied by over half of the cases of IIM and most of them had autoantibodies. There are characteristic clinical features by onset time of ILD, so paying attention to them will help early diagnosis and prognosis prediction of ILDs. Reference: [1] Yoshifuji H. Clin Med Insights Circ Respir Pulm Med. 2016 Apr 3;9 (Suppl 1):141-6. Disclosure of Interests: None declared